Maternal Sociodemographic Parameters: Impact on Trace Element Status and Pregnancy Outcomes in Nigerian Women (Journal of Health, Population and Nutrition, 2011)
To determine the impact of socioeconomic status on plasma trace element status and pregnancy outcomes, 349 pregnant women, aged 15-40 years (mean 27.04 ±2.75 years), recruited at ≤25 weeks (mean 21.76±3.12 weeks) gestational age, were followed up till delivery during which maternal and foetal outcomes were recorded. Plasma copper, iron, and zinc were determined using atomic absorption spectrophotometer while maternal sociodemographic data were obtained using a questionnaire. Except for copper, lower plasma iron and zinc were significantly (p